Performance of peppers produced in the Sub-Middle São Francisco valley under semi-protected cultivation (Research, Society and Development, 2020)
The production of vegetables is a very advantageous agricultural activity when practiced in suitable seasons and climatic conditions, however, one of the ways to circumvent environmental adversities is the practice of cultivation in a protected and semi-protected environment. The present work aimed to determine the type of covering material suitable for the cultivation of the pepper culture in a semi-protected environment in the region of the Submédio São Francisco valley. The experiment was carried out in the DTCS / UNEB experimental field in a randomized block design in a 5 x 2 factorial scheme with 3 replications. The treatments consisted of five environments with four different cover materials (thermal reflective screen; white screen; black screen and chromatography screen, all with 40% shading and as a treatment witness the open air cultivation and two pepper hybrids (AF-7125 and LUCIA-R), three harvests were carried out starting at 88 DAT, and the following characteristics were evaluated: fruit classification, fruit length and diameter (mm), pulp thickness (mm), production per plant (g plant-1 ), number of fruits per plant, average fruit weight (g), productivity (t ha-1), water use efficiency (kg m3) and volume of water applied (mm). better agronomic performance and greater efficiency in the use of water than those produced in the open.